Over-expression of tau results in defective synaptic transmission in Drosophila neuromuscular junctions. - Chee, F.C.; Mudher, A.; Cuttle, M.F.; Newman, T.A.; MacKay, D.; Lovestone, S.; Shepherd, D. (Neurobiology of Disease, 2005)
We have shown that over-expression of human tau (0N3R) in Drosophila larval motor neurons causes significant morphological and functional disruption to the neuromuscular junctions (NMJs). Tau-expressing NMJs are reduced in size with irregular and abnormal bouton structure. Immunocytochemical analysis shows that the abnormal NMJs still retain synaptotagmin expression and form active zones. Functionally, the NMJs exhibit abnormal endo/exocytosis as revealed by incorporation of the styryl dye FM1-43. Electrophysiological studies showed that with low frequency stimulation (1 Hz), evoked synaptic potentials produced from tau over-expressing motor neurons were indistinguishable from wild type, however, following high frequency stimulation (50 Hz), evoked synaptic potentials were significantly decreased. Analysis of the number and distribution of mitochondria showed that motor neurons over-expressing tau had a significant reduction in functional mitochondria in the presynaptic terminal. Collapsing the mitochondrial membrane potential in wild type larvae phenocopied the effects of tau over-expression on synaptic transmission. Our results demonstrate that tau over-expression in vivo cause a synaptic dysfunction, which may be caused by a reduced complement of functional mitochondria.